GCM simulations of anthropogenic aerosol‐induced changes in aerosol extinction, atmospheric heating and precipitation over India. Issue 7 (15th April 2013) - Cherian, Ribu; Venkataraman, C.; Quaas, J.; Ramachandran, S.
Abstract : [1] The influence of anthropogenic emissions on aerosol distributions and the hydrological cycle are examined with a focus on monsoon precipitation over the Indian subcontinent, during January 2001 to December 2005, using the European Centre for Medium‐Range Weather Forecasts‐Hamburg (ECHAM5.5) general circulation model extended by the Hamburg Aerosol Module (HAM). The seasonal variability of aerosol optical depth (AOD) retrieved from the MODerate Resolution Imaging Spectroradiometer (MODIS) on board the Terra and Aqua satellite is broadly well simulated ( R ≈ 0.6–0.85) by the model. The spatial distribution and seasonal cycle of the precipitation observed over the Indian region are reasonably well simulated ( R ≈ 0.5 to 0.8) by the model, while in terms of absolute magnitude, the model underestimates precipitation, in particular in the south‐west (SW) monsoon season. The model simulates significant anthropogenic aerosol‐induced changes in clear‐sky net surface solar radiation (dimming greater than −7 W m −2 ), which agrees well with the observed trends over the Indian region. A statistically significant decreasing precipitation trend is simulated only for the SW monsoon season over the central‐north Indian region, which is consistent with the observed seasonal trend over the Indian region. In the model, this decrease results from a reduction in convective precipitation, where there is an increase in stratiform cloud droplet number concentration (CDNC) and solar dimming that resulted from increased stability and reduced evaporation. Similarities in spatial patterns suggest that surface cooling, mainly by the aerosol indirect effect, is responsible for this reduction in convective activity. When changes in large‐scale dynamics are allowed by slightly disturbing the initial state of the atmosphere, aerosol absorption in addition leads to a further stabilization of the lower troposphere, further reducing convective precipitation. Key Points: Anthropogenic aerosols reduce precipitation over central‐north India 90% rainfall reduction resulted from convective precipitation Surface cooling from aerosol indirect effects responsible for rainfall reduction